1985
DOI: 10.1177/017084068500600302
|View full text |Cite
|
Sign up to set email alerts
|

Outside the Goal Paradigm: Power and Structured Patterns of Non-Rationality

Abstract: It is argued that power is a better explanatory factor in organizational analysis than are 'goals' or 'rationality'. This is supported by examples from the author's research in social-work organizations. These examples illustrate some of the ways that power is organized in what recent writers have called 'loosely coupled', 'street-level' bureaucracies.Informal and spontaneous organizing practices as well as rituals decide real (as distinct from formal ) power and control at the operating level. For the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Additionally, Boynton and Zmud (1987) observed that professionals who work with information systems face increased loose coupling between subunits when personal computers are dispersed throughout organizations. Sunesson (1985) suggested that "street-level bureaucracies" (p. 243) lead to loose coupling between goals and actions, whereas Raghunathan and Beekun (1989) proposed that the ownership coupling patterns of multinational corporations are a function of the maturity and cultural diversity of subsidiaries. Finally, Thomas (1983) described the Chicago Eight trial as a competition for control of proceedings and meanings that created loose couplings between judicial practices and the ideological premises of due process.…”
Section: Fragmented Internal Environmentmentioning
confidence: 99%
“…Additionally, Boynton and Zmud (1987) observed that professionals who work with information systems face increased loose coupling between subunits when personal computers are dispersed throughout organizations. Sunesson (1985) suggested that "street-level bureaucracies" (p. 243) lead to loose coupling between goals and actions, whereas Raghunathan and Beekun (1989) proposed that the ownership coupling patterns of multinational corporations are a function of the maturity and cultural diversity of subsidiaries. Finally, Thomas (1983) described the Chicago Eight trial as a competition for control of proceedings and meanings that created loose couplings between judicial practices and the ideological premises of due process.…”
Section: Fragmented Internal Environmentmentioning
confidence: 99%
“…Other authors have also suggested the political model as an alternative to the traditional approach (Narayanan and Fahey 1982;Sunesson 1985). They suggested that, in reality, organizational decisions reflect a process of power struggle among conflicting individuals and groups, attempting to further their own self-serving goals.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in their comparison of nonprofits funded with block grants and nonprofits with service-based funding (such as government contracting), Berg and Wright (1980) (Harlan and Saidel, 1996; and have documented a variety of responses to funder requirements (Bigelow and Stone, 1995). Research on responses to centralized directives suggests that units with strong ideological and task paradigms that conflict with directives will resist (Sheinfeld and Weirich, 1981;Sunesson, 1985). Similarly, decision making in response to funder pressures in community health centers is explained better by organizational values and norms than by funder demands (Bigelow, 1990).…”
Section: Role Of Funding Sourcesmentioning
confidence: 99%